1996
DOI: 10.1177/003693309604100605
|View full text |Cite
|
Sign up to set email alerts
|

SKI Injuries in Scotland a Review of Statistics from Cairngorm SKI Area Winter 1993/94

Abstract: Scottish skiing is a growth industry-nearly all acute ski injuries in Aviemore are managed initially by local general practitioners. This study set out to examine the nature and incidence of ski injuries in one Scottish ski resort, and to calculate the additional workload generated for the health centre, ambulance service and local hospital. During the study period, the winter ski season of 1993-94, a prospective study was made of the 486 acute ski injuries presenting to Aviemore Health Centre. Despite frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Two previous publications have reported on the patterns of injury seen at separate Scottish ski areas. 12 13 The results were comparable to those from other areas, but both had limitations in their study design, principally the lack of control data. Subsequently, there has been a perceived growth in the popularity of snowboarding and skiboarding in Scotland.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Two previous publications have reported on the patterns of injury seen at separate Scottish ski areas. 12 13 The results were comparable to those from other areas, but both had limitations in their study design, principally the lack of control data. Subsequently, there has been a perceived growth in the popularity of snowboarding and skiboarding in Scotland.…”
supporting
confidence: 71%
“…In 1994, snowboarders accounted for only 4% of the injured population at Cairngorm. 12 Although we registered relatively few on piste telemark ski injuries, many participants ski away from designated ski areas, and the injury rate in this population in Scotland remains unknown. Males comprised the majority of all our injured groups, but we found no difference between the sex constituencies of any injured and control group.…”
Section: Discussionmentioning
confidence: 99%
“…The overall risk of injury at a Scottish ski area has been consistently demonstrated to be comparable with that of other areas worldwide. 22,23,32 Several independent risk factors for snow sports injury in Scotland have been identified, including 1st-day participation and age younger than 16 years. 23 This larger study has confirmed our previous finding of an excess injury risk among FDP and has identified several independent risk factors for injury among this population.…”
Section: Discussionmentioning
confidence: 99%
“…The higher rate of head and facial injuries among non-FDP skiers can be at least partially explained by the fact that, in Scotland, the majority of these injuries result from a carelessly discarded T-bar. 22 Given their inherent difficulty in use, these lifts are unlikely to be used by FDP skiers. Most ski injuries were soft-tissue sprains, and skiing has the lowest incidence of fractures among the three snow sports, with FDP skiers being at least risk.…”
Section: Discussionmentioning
confidence: 99%